Influence of urbanization-driven water quality on reef substrate composition along Suva, Fiji, one of the Pacific Islands most urbanized reefs - Dehm, Jasha; Ford, Amanda K.; Singh, Awnesh; Lal, Monal (Frontiers in Marine Science, 2025)
Anthropogenic stressors, including those associated with water quality influence reef benthic communities. This study assesses how changes in water quality influence the benthic composition of an urban reef system in Fiji, by first characterizing reef substrate composition in Suva, assessing substrate composition change across a water quality gradient, and identifying key water quality parameters associated with shifts in benthic composition. Results reveal an urban reef stabilized at coral coverage of ca. 30%, below Fiji’s typical range (45%), but consistent with prior levels (22–33%) from 2006-2007. Predictive modelling identifies temperature as the most consistent predictor of benthic composition (appearing in 77.5% of top models), highlighting its role in structuring communities through physiological and nutrient-cycling effects. Turbidity and nutrients further drive substrate patterns, with turbidity likely promoting sediment accumulation, and elevated nutrients influencing phase shifts towards alternative regimes. Our results demonstrate how urbanization filters benthic communities, creating distinct configurations with varying resilience. Notably, sites with moderate anthropogenic stress levels are characterized by the coexistence of scleractinian coral, seagrass, and soft coral, differing from typical coral-to-algae dominance shifts. While Suva’s reefs currently persist in a degraded-but-stable state, sustained pressures risk further decline. We emphasize targeted strategies (e.g., reef crest protection, watershed management) and long-term monitoring to inform adaptive management. These insights are critical for Fiji and other Pacific Island nations facing similar urban reef stressors, offering a framework for balancing conservation with development.